2020
DOI: 10.1089/hum.2019.206
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Bid Regulates Cisplatin Response via Activation of Mitochondrial Apoptosis Pathway in Ovarian Cancer

Abstract: Refractoriness to conventional chemotherapy is a major challenge in the treatment of advanced ovarian cancer (OC). There is increasing evidence that mitochondrial priming correlates with cisplatin response in various cancers. Notably, Bim and Bid, two of the proapoptotic BH3-only proteins, are recognized as the most effective inducers of mitochondrial priming in OC. In this study, we constructed two tumor-specific oncolytic adenoviruses (Ads) coding for Bim (Ad-Bim) or truncated Bid (Ad-tBid), respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…BId is considered to be the most effective initiator among BH3-only proteins. When constructed into tumor-specific oncolytic adenoviruses, the overexpression of BId exhibited great antitumor activation and enhanced the chemosensitivity to cisplatin in 9 ovarian cancer cell lines, consistent with the effect in a subcutaneous tumor xenograft model (68).…”
Section: Bcl-2 Family Members In Ovarian Cancersupporting
confidence: 61%
“…BId is considered to be the most effective initiator among BH3-only proteins. When constructed into tumor-specific oncolytic adenoviruses, the overexpression of BId exhibited great antitumor activation and enhanced the chemosensitivity to cisplatin in 9 ovarian cancer cell lines, consistent with the effect in a subcutaneous tumor xenograft model (68).…”
Section: Bcl-2 Family Members In Ovarian Cancersupporting
confidence: 61%
“…Since cell apoptosis is involved in CP-induced mitochondrial dysfunction, which is accompanied by the loss of MMP [ 26 28 ], we next explored whether PSF-SOD1 could restore CP-induced MMP decrease. Control cells stained with JC-1 exhibited strong red fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the in vitro and in vivo application of Ad-p53 resulted in the activation of apoptosis and taxolsensitisation in ovarian cancer cells [38], while Gendicine, a gene therapy product approved for clinical use by the Chinese FDA in 2003, is now demonstrating very promising results, leading to a 90% patient response rate and 100% peritoneal effusion resolution [37]. In a recent study, Dai et al [36] constructed two tumour-specific oncolytic adenoviruses coding for Bim (Ad-Bim) or truncated Bid (Ad-tBid) and performed gain-of-function assays in nine ovarian cancer cell lines. The authors observed increased cisplatin sensitisation and apoptosis following treatment with Ad-tBid in vitro and ex vivo, while following Ad-tBid intraperitoneal administration in mice with peritoneal disseminated ovarian cancer, they observed enhanced cisplatin-mediated anti-tumour effects [36].…”
Section: Retrovirusesmentioning
confidence: 99%
“…In a recent study, Dai et al [36] constructed two tumour-specific oncolytic adenoviruses coding for Bim (Ad-Bim) or truncated Bid (Ad-tBid) and performed gain-of-function assays in nine ovarian cancer cell lines. The authors observed increased cisplatin sensitisation and apoptosis following treatment with Ad-tBid in vitro and ex vivo, while following Ad-tBid intraperitoneal administration in mice with peritoneal disseminated ovarian cancer, they observed enhanced cisplatin-mediated anti-tumour effects [36]. Lastly, in regard to the immunopotentiation approach, HER2/neu, a protein shown to be overexpressed in ovarian cancer [79], was delivered to dendritic cells (DCs) by an AAV and primed these cells to express a self-tumour antigen.…”
Section: Retrovirusesmentioning
confidence: 99%